Private Litigation to Enforce Fiduciary Duties in Mutual Funds: Derivative Suits, Disinterested Directors and the Ideology of Investor Sovereignty - Donald C. Langevoort (Washington University Law Quarterly, 2005)
The aim of this paper is to critique some of the key judicial steps, with particular attention to private securities litigation that takes the form of a derivative action on behalf of a particular fund. My critique will not dwell on the pending cases directed against the late trading and market timing abuses in any great detail, although these surely are important. As New York Attorney General Elliot Spitzer emphasized in his remarks and enforcement philosophy after exposing the misbehavior, these issues— though involving many hundreds of millions of dollars in the aggregate— were relatively small compared to other matters of concern in an 8 trillion industry. The broader issues involve fiduciary responsibility across a wide range of matters including management fees, distribution expenses, brokerage commissions, and the like. This article focuses on independent directors and the processes of mutual fund corporate governance. To be clear, I believe (and research shows) that disinterested directors do add value as a form of shareholder protection, and this fact justifies the SEC’s efforts to strengthen their role. But they are far from a panacea. While that point alone is almost trite, exploring some of the unique features of mutual fund governance shows why judges and policymakers should not even try to reason by analogy to governance in other kinds of corporations. Yet that is exactly what Burks and its progeny have done. Even more interesting is considering the governance consequences of the primary distinction between mutual funds and business corporations: the convergence of the capital and product markets that occurs when the products being sold by the mutual fund are its own securities. Here, the ideology of consumer sovereignty easily crowds out a strong norm of fiduciary responsibility. “Disinterested” directors see little need to measure the behavior of the fund’s advisor by reference to anything other than marketplace success—and indeed can be chosen precisely because they embrace the ideology of the markets and see the law’s assignment to them of strong fiduciary responsibilities as something of an exercise in formalism. If this happens, as I suspect is commonplace, then their checking power will be moderate at best, and the case law’s assumption of more, the basis for the decreasing judicial oversight we have seen over the last twenty-five years, misplaced.
Keywords: Fiduciary responsibility; Stockholders& #x27; derivative actions; Breach of trust; Corporate governance; Disclosure (Securities law); Fiduciary duties; Mutual funds; Shareholder lawsuits; Investment Company Act of 1940; United States